2012
DOI: 10.4103/0019-509x.102867
|View full text |Cite
|
Sign up to set email alerts
|

Carcinoma base of tongue: Single institution 15 year experiences

Abstract: In locally advanced squamous cell carcinoma of base of tongue tumors concomitant chemoradiotherapy with infusional cisplatinum and 5 fluorouracil results in higher disease free and overall survival as compared to radiotherapy as single modality. This better tumor response with chemoradiotherapy comes at cost of higher incidence of mucosal toxicity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
2
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 21 publications
2
2
0
Order By: Relevance
“…This study found that tumour size (T stage) and the presence of lymph nodes at diagnosis (N stage) were significant predictors of patient outcomes. This finding indicates that T and N stages can be considered independent factors prognostic of overall survival in this group of patients and that patients without lymph node metastases at initial diagnosis and with T1 or T2 tumours have a higher survival rate (64.92%), confirming previous results ( 10 , 18 ).…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations
“…This study found that tumour size (T stage) and the presence of lymph nodes at diagnosis (N stage) were significant predictors of patient outcomes. This finding indicates that T and N stages can be considered independent factors prognostic of overall survival in this group of patients and that patients without lymph node metastases at initial diagnosis and with T1 or T2 tumours have a higher survival rate (64.92%), confirming previous results ( 10 , 18 ).…”
Section: Discussionsupporting
confidence: 89%
“…After analysing the high mortality rates evidenced in this study and the published reports, it can be concluded that this is a serious disease because of the difficulties of access to adequate treatment, medical professionals often not able to make the appropriate initial diagnosis, and neglect of patients not seeking care but having habits that trigger the disease, corroborating with several surveys ( 10 - 18 ).…”
Section: Discussionsupporting
confidence: 85%
See 2 more Smart Citations